KERUDUNG SANTET GANDRUNG : SIMBOL PERLAWANAN TERHADAP KAUM SANTRI BANYUWANGI - Sungkowati, Yulitin (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2007)
A literary work as a cultural artifact is a verbal symbol that has to beinterpreted in a broad context because it correlates with the writer's intention inresponding to an experienced situation. Kerudung Santet Gandrung is a novel setin Banyuwangi representing the life of practitioners of the Gandrung traditional artand that of santris, people studying at Islamic religious boarding schools. Thereare many symbols in the novel which potentially could be seen as indications oftextual elements in the dynamic relation between the two different communities.By using a cultural hermeneutic approach, the novel strives to depict an effort inresistance made by Hasnan Singodimayan, an observer of Banyuwangi culture, toreconstruct a new and positive image of traditional artists. His resistance is anattempt to preserve Banyuwangi traditional arts which are threatened withextinction by Islamic purification movements.Keywords: novel, Gandrung, symbol, resistance